Field research to ensure the safety of the earth dam - Paluanov Daniyar; Mamatkulov Dilmurat; Gadaev Sodik; Saidov Farid (E3S Web of Conferences)
One of the ways to ensure the safe condition of earth dams during operation is to conduct field investigations on the structure. One of the factors leading to water spillage over the dam crest is the determination of settlement in the body of the earth dam. The assessment of excessive settlements in reservoir earth dams is based on observation data and project documentation. In practice, the settlement of earth dams during the operational period should not exceed the values specified in the project. Settlement measurements for the embankment body are carried out based on requirements specified in regulatory documents. The Langar Reservoir is located in the Langar River bed in the Kashkadarya region. The facility was built in 1971-1973. It was put into permanent operation in December 1973 with a design capacity of 4.0 million m3 as a mudflow storage facility. Repeat geodetic measurements (second cycle) were conducted to determine the settlement of the dam crest. According to the geodetic measurements, the settlement of the dam crest during the observation period was 15 mm in the first cycle and 18 mm in the second cycle.